Linear and nonlinear experiments in PT-Symmetric photonic mesh lattices - Wimmer, Martin; Christodoulides, Demetrios; Peschel, Ulf (Parity-time Symmetry and Its Applications, 2018)
Photonic mesh lattices provide a versatile experimental platform for studying light propagation in a discrete environment. By using standard telecommunication equipment it is possible to influence the evolution of light by actively modulating its amplitude and phase. Fiber components thus offer a ready to use solution for creating a PT -symmetric optical network. Here, we analyze two classes of PT -symmetric networks: Those with local PT symmetry fulfilling the conditions of PT symmetry in each time step but not globally and those with global PT symmetry providing completely real eigenvalues. We investigate light propagation in these dissipative media in the linear and nonlinear regime and discuss nonlinear localization as well as the formation of soliton. Furthermore, Bloch oscillations are induced by an external phase modulation and are found to restore pseudo-Hermitian propagation.
CRIS-Team Scopus Importer:2023-04-20